Perancangan Ekspektasi Biaya Total Tahunan dengan Alternatif Jalur Pasokan Model Persediaan Jenjang Jamak - Albertus Magnus Madyana (Universitas Bunda Mulia, 2017)
Production and distribution activities in production system need to be integrated in order to increase the efficiency of the system effectively, and to decrease the cost of logistics flow. In an echelon inventory model, it can be planned and controlled, so the size of order lot for each distribution service system unit can be integrated in a value chain system. By understanding which supply channel that produce annual minimum cost, we can decide which policy of supply channel and optimal lot to be implemented.Keywords: Echelon Inventory Model, Optimization of Minimum Cost